Isolation of Fe(III)-reducing bacterium, Citrobacter sp. LAR-1, for startup of microbial fuel cell. (23rd February 2016) - Liu, Lihong; Lee, Duu-Jong; Wang, Aijie; Ren, Nanqi; Su, Ay; Lai, Juin-Yih
Abstract: The LAR-1 strain was isolated from sediment samples collected at the– intersection of A-Shi River and Songhwa River, China with high iron-reducing capability. Biochemical tests (API 20A, API-20NE and API-ZYM), fatty acids analysis, and polymerase chain reaction (PCR)-denaturing gradient gel electrophoresis (DGGE) tests revealed that LAR-1 is closely related to Citrobacter sp. The LAR-1 was used as anode chamber seed to start up microbial fuel cell (MFC). The tested MFC had an open-circuit voltage of 610 mV and a maximum power density of 610 mW/m 2 at 360 mV. The analytical results confirmed that the iron-reducing bacterium can be used as anodic respiratory bacterium for MFC. Highlights: An iron-reducing bacterium, LAR-1, was isolated from sediment samples. The LAR-1 was used successfully as anodic aspirating bacterium in MFC. The LAR-1-MFC hasOCV of 610 mV and maximum power density of 610 mW/m 2 . The iron-reducing bacterium can be used to start up MFC.